The Factors That Determine Employee Job Satisfaction At Pandawa All Suite Hotel - I Wayan Ruspendi Junaedi; I Made Darmayasa; Ni Kadek Susi Susanti; Gilbert Nainggolan (Asian Journal of Management, Entrepreneurship and Social Science, 2022)
ABSTRACT Pandawa All Suite Hotel is an accommodation designed to be the hotel of choice for guests who want to have a relaxing time with quality service and a friendly environment. Pandawa All Suites Hotel is committed to providing a quiet and comfortable stay. This study aims to determine the factors that specify employee job satisfaction at the Pandawa All Suite Hotel. This type of research uses qualitative and quantitative data, using data sources namely primary data and secondary data. The sampling method used in this study is Saturated Sampling with 40 respondents. The analytical tools used is the Validity Test and Reliability Test, quantitative descriptive analysis, factor analysis and data processed using SPSS Version 17 software for windows. The results obtained after analysis using a factor analysis of 16 variables that determine employee job satisfaction at the Pandawa All Suite Hotel into 3 factors: compensation factors have an eigen value of 7,810, leadership factors have an eigen value of 1,511 and the last factor is work equipment with value eigen value 1,222. This study shows that the most dominant factor determining employee job satisfaction at the Pandawa All Suite Hotel is the compensation factor that has the highest value of the overall eigen value 7,810. Keywords : Factor Determine, Employee, Job Satisfaction, Pandawa